GENETICALLY MODIFIED ORGANISMS AND THEIR IMPACT ON INTERNATIONAL AGRICULTURAL TRADE: A CASE STUDY ON SOY (Revista de Estudos Sociais, 2019)
This paper discusses the introduction of genetically modified (GM) seeds in agriculture and their impact on the modus operandiof international trade of agricultural commodities. The central argument in this paper is that the commercial rejection by some markets, especially in the European Union, resulted in broad market share restructuring of the three largest international soy exporters: the United States, Brazil, and Argentina. These findings came as a result of trade flow analysis, taking into account the source and destination of soy in the soy trade using the quantitative Constant Market Share method. Taking into account that at the time of the study there were no legal trade barriers put up by the European Union, which was resistant to the use of Monsanto’s herbicide-tolerant soy (GTS-40-3-2), it is assumed that the effects resulting from its commercial rejection were due to demand factors and not for any official trade ban. It is concluded that technology adoption caused changes in factors that led to export growths. However, despite changes in market share, the globalization effect prevented exporters from incurring greater trade losses since they always had the option of moving their products to markets with lower levels of “hatred”.